We can rewrite
![]() | (C.1) |
with, for ξ0′ > ξ0T ,
![]() | (C.2) |
where
![]() | (C.3) |
In the limit ϵ ≪ 1, we have
Ψ | ≡![]() | ||
= ![]() ![]() | |||
= 1 + ϵ![]() ![]() ![]() | (C.4) |
so that
ξ′ | = ![]() | ||
= ξ0′![]() |
In fact, the series expansion of the square root must be kept to all orders for the term in ϵ, because the ratio ϵ∕ξ0′2 → 1 for ξ0′→ ξ0T . This gives
where we used
![]() | = 1 + ∑
n=1∞![]() | (C.5) |
![]() | = 1 + ∑
n=1∞![]() ![]() ![]() ![]() ![]() | (C.6) |
= 1 + ![]() ![]() ![]() ![]() ![]() ![]() ![]() | (C.7) | |
= 1 + ![]() ![]() | (C.8) | |
= 1 + ∑
n=2∞![]() | (C.9) |
In addition,
![]() | = ![]() | ||
= 1 - ϵ![]() ![]() ![]() | (C.10) |
We get
λ2,-1,0![]() | = ∫
02π![]() ![]() | (C.11) | |
= ∫
02π![]() ![]() | |||
![]() | (C.12) | ||
= 1 -∑
n=1∞λ
2,-1,0(n)![]() ![]() ![]() | (C.13) |
with
λ2,-1,0(1)![]() | = ∫
02π![]() ![]() ![]() | (C.14) |
= ![]() ![]() | (C.15) |
and, for n ≥ 2,
λ2,-1,0(n≥2)![]() | = ∫
02π![]() ![]() ![]() | (C.16) |
= ![]() ![]() ![]() ![]() | (C.17) | |
= ![]() ![]() ![]() ![]() | (C.18) | |
= ![]() ![]() ![]() | (C.19) |
We can transform, for n ≥ 2,
Y n | = ∫
0π![]() | ||
= ∫
0π![]() | |||
= ![]() ![]() ![]() | |||
= ![]() ![]() | |||
= ![]() ![]() |
so that
with
so that
Y n | = ![]() ![]() ![]() ![]() ![]() ![]() | ||
= ![]() | |||
= ![]() |
and we find
λ2,-1,0(n≥2)![]() | = ![]() ![]() | (C.20) |
= ![]() ![]() | (C.21) |
We obtain
I![]() | = ![]() ![]() | ||
= ![]() ![]() | |||
= ∫
ξ0Tξ0
dξ0′![]() | |||
= ξ0 -![]() ![]() ![]() ![]() ![]() |
with
where we used
![]() | = 1 + ∑ m=1∞xm | (C.22) |
ξ0T | = ![]() ![]() ![]() | (C.23) |
![]() | = ![]() ![]() | (C.24) |
We have
Clearly, the only term of order ϵ-1∕2 comes from the ξ0′-2 contribution integrated and taken on ξ0T . We need to keep only
I![]() ![]() | = ∫
ξ0Tξ0
dξ0′![]() ![]() ![]() | ||
= ∫
ξ0Tξ0
dξ0′![]() ![]() ![]() | |||
= ∫
ξ0Tξ0
dξ0′∑
i1=1∞∑
i2=1∞![]() ![]() ![]() ![]() ![]() ![]() ![]() | |||
= ∑
i1=1∞∑
i2=1∞![]() ![]() ![]() ![]() ![]() ![]() ![]() | |||
= ∑
i1=1∞∑
i2=1∞![]() ![]() ![]() ![]() ![]() | |||
= ![]() ![]() ![]() ![]() ![]() |
with
and finally we get
∫
-11dξ
0σξ0H![]() ![]() | |||
= 2∫
ξ0T1dξ
0ξ02 - ξ
0ϵ1∕2![]() | |||
×![]() ![]() ![]() | |||
= ![]() ![]() ![]() ![]() ![]() |
and therefore
![]() | (C.25) |
with
For example, C1 = 1∕2, C2 = 3∕16, C3 = 5∕32,
m | i1 | i2 | correction |
1 | 1 | - | 1∕4 |
1 | 2 | - | 1∕64 |
1 | 3 | - | 1∕256 |
1 | 4 | - | 25∕16384 |
1 | 5 | - | 17∕22737 |
2 | 1 | 1 | 1∕48 |
2 | 1 | 2 | 3∕1280 × 2 |
2 | 2 | 2 | 9∕28672 |
2 | 1 | 3 | 5∕7168 × 2 |
2 | 2 | 3 | 5∕49152 × 2 |
2 | 3 | 3 | 6∕173015 |
The sum of all these coefficient gives K = 1.486, which is already much better that
9∕8 = 1.591
We compute the coefficient K for several values of the highest terms M and N in the series (C.25). The results are shown on Fig. C.1. We first see that K converges for high M and N, towards a value that seems close to 1.46. The best combination seems to be for M = N, as both high M and high N are needed for convergence. Therefore, we take M = N and calculate K as a function of M. Results are shown on Fig. C.2. We can see that K indeed converges, and that the asymptotic limit is about K = 1.46. For M = N = 6, we find K = 1.467.